Pengaruh Motivasi Kerja, Disiplin Kerja dan Kepuasan Kerja terhadap Kinerja: The Effect Of Work Motivation Work Discpiline and Work Satisfaction On Ferformance - Milang, Ichsan; Maay, Hany Natalia; Suong, Fatha Putri Asrun (Jurnal Ilmiah Produktif, 2023)
The formulation of the problem is how work motivation, work discipline and job satisfaction have a significant effect on performance partially and simultaneously at the Luwuk Village Office. The type of data is qualitative which is quantified with a sample of 10 respondents. The analysis tool is a multiple linear regression test with the equation form Y = 20.934 - 5.575X1 + 6.682X2 - 1.038X3, correlation coefficient, determination coefficient, t test and f test. The results of the t test are the T value of Work Motivation of -2.590 with a significance level of 0.041, Work Discipline of 3.065 with a significance level of 0.022, Job Satisfaction of -3.082 with a significance level of 0.022. T table of 2.447 (t count > t table). The result of the F test is 8.313 with sig 0.015, F table is 4.76, so there is a significant influence between Work Motivation (X1, Work Discipline (X2), Job Satisfaction (X3), and Performance (Y). The determination coefficient is 80.6% and the remaining 19.4% is influenced by other variables not studied. The correlation coefficient is 0.898, indicating a very strong relationship.